Karakteristik Partus Prematurus Imminens di Rspal Dr Ramelan Surabaya Periode Juni 2019 – Juni 2020 - MALIKU NURROCHMAN WIDANDI; MITA HERDIYANTINI; KETUT EDY SUDIARTA (Universitas Hang Tuah, 2022)
Background: The child mortality rate in the world and in Indonesia in particular is still high. Based on WHO data, Indonesia is in the top 10 countries with a total of 675,700 cases of premature birth. Premature labor is often preceded by signs of labor called Threatened Preterm Labor. Threatened Preterm Labor is the occurrence of a threat of labor in the form of uterine contractions and/or other signs of labor at gestational age between > 20 - < 37 weeks. If it does not get adequate treatment, it is often followed by premature birth. Prematurity increases the rate of cesarean delivery and increases child mortality. This study aims to determine the characteristics of pregnant women with Threatened Preterm Labor at RSPAL Dr. Ramelan Surabaya. Methods: This research is a descriptive study using purposive sampling technique. The research sample used Threatened Preterm Labor cases recorded in the medical records of RSPAL Dr. Ramelan Surabaya. Results: The results showed that 50 cases of Threatened Preterm Labor. Most of them occurred at the age of 20 - 35 years as many as 39 (78%), with a high school education level of 31 (62%), as many as 26 patients (52%) worked. Based on parity, most occurred in primiparous as many as 19 cases (38%). Based on ANC visits, the majority of patients who did not perform ANC were 43 patients (86%). Most of them had normal blood pressure as many as 37 patients (74%), 30 patients (60%) had low hemoglobin levels / anemia, and 29 patients (58%) had normal leukocyte levels. Most previous pregnancy history in normal pregnancy was 28 cases (56%). A total of 31 patients (62%) had complications in pregnancy. The success of tocolytic therapy was 34 cases (68%). Conclusion: Eighty-six percent of PPI patients admitted to RSPAL never had ANC, 60% of the samples were included in the anemia category, and 62% were motivated by complications of this pregnancy including premature rupture of membranes (PROM), preeclampsia, gemelli, gestational diabetes, infection, anemia, and polyhydramnios. Suggestion: more intensive public health education is needed, especially for pregnant women.